Mitigation of Impulsive Transient Effect in Solar Photovoltaic System Caused by Lightning - Nazri, Rasydan; Dur Muhammad Soomro, (Evolution in Electrical and Electronic Engineering, 2022)
Solar photovoltaic (PV) system is a form of renewable energy that is constantly utilized to generate electricity. Due to their openness to the outside environment, PV systems are at significant risk of being struck by lightning. Lightning may cause serious damage to solar panels; thus, lightning protection should be considered early in the design process. This project includes the study of the power quality (PQ) problem create by lightning with calculation to produce impulsive transient using an RC circuit. Without the use of a surge protector, The PV system poses a risk of electrical device damage, as well as the risk of fire. A surge protection device (SPD) is a protective device for electrical equipment that protects them against impulsive transients. This project will use Type 2 SPD to prevent the spread of overvoltage in electrical networks and to protect equipment connected to them. It has a 1./50μs voltage wave and is frequently constructed using metal oxide varistor (MOV) technology. MATLAB Simulink is used to simulate the test case for the project. The project's results show steady-state output waveforms, a distorted wave of power quality problems caused by lightning, and mitigated results when the mitigation method was applied.